An efficient and eco‐friendly solution‐chemical route for preparation of ultrastable reduced graphene oxide suspensions. Issue 8 (29th May 2014) - He, Dafang; Shen, Liming; Zhang, Xiaoyan; Wang, Yifeng; Bao, Ningzhong; Kung, Harold H.
<x xml:space="preserve">Abstract</x> We describe a facile and eco‐friendly solution approach to chemically reduce graphene oxide (GO) to high‐quality graphene using nontoxic inexpensive reductants. The reduction process and mechanism of a group of eco‐friendly reductants were systematically studied. These reductants perform quite differently in terms of reduction rate (l‐ascorbic acid [l‐AA] > d‐fructose > sucrose > glucose > sodium sulfite), density of small sp2 domains (l‐AA > sodium sulfite > glucose > sucrose > d‐fructose), degree of reduction (l‐AA > glucose > d‐fructose > sodium sulfite > sucrose), and stability of the reduced GO suspension (l‐AA > d‐fructose > sucrose > glucose > sodium sulfite). l‐AA shows the highest reducing ability, achieving the largest extent of reduction after 10 min in the presence of ammonia. Both residual oxygen functionalities and the adsorbed oxidization products of l‐AA on the graphene surface are responsible for stabilizing the reduced GO suspension over several months. © 2014 American Institute of Chemical Engineers AIChE J, 60: 2757–2764, 2014